Analysis On Study Address Terms and Gender Dyanamic Found In Mambalan: A Pragmatic Study - Miswaty, Titik Ceriyani; Sugianti, Linda; Arsinabila, Oyi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Address terms and politeness strategies play a crucial role in communication, reflecting social relationships, cultural norms, and gender dynamics. This study investigates the use of address terms in Mambalan, a village in West Nusa Tenggara, Indonesia, within the context of Sasaknese language, gender roles, and sociocultural influences. Address terms in Mambalan are shaped by age, class, and relational context, demonstrating an interplay between traditional values and modernization. The research draws on Brown and Levinson's politeness theory, focusing on strategies such as positive and negative politeness to explore how language maintains social